Microbial Evaluation of Turkish Herbal Teas Before and After Infusion - OMURTAG KORKMAZ, BURCU İREM; AKDUMAN, GÜL (My University, 2020)
Background: Herbal teas are produced and sold in packaged or unpackaged forms all over the world. The aim of this study was microbial evaluation of Turkish herbal teas before and after infusion in boiled water. Methods: A total of 20 packaged and unpackaged samples of Turkish herbal teas, including chamomile, salvia, green, mix, apple, mate, ginger, linden, fennel, and senna tea were collected. All of the samples were analyzed before and after infusion in hot water (~100 °C). Microbiological analyses were performed with tenfold serial dilution for yeast-mold, Salmonella, and Cronobacter sakazakii after enrichment by using the spread-on-plate method on selective agar. Data were statistically analyzed by using Microsoft Office Professional Plus 2013 Excel software. Results: Three out of the 20 tea samples (15%) were contaminated with C. sakazakii. None of the samples were contaminated with Salmonella spp. No significant difference was found in occurrence of C. sakazakii before and after infusion of the samples (p>0.05). Mold and yeast contamination were found in 12 out of 20 teas samples (60%). No statistical significance (p>0.05) was found between the mold-yeast contents of the unpackaged and packaged herbal teas. After infusion, neither mold nor yeast was observed in any of the samples. Conclusion: All of the herbal teas in this research were found to be within the microbiological limits for consumption according to Turkish Food Codex. However, the microbiological results highlighted the need for quality control of senna tea during production to eliminate the risk of C. sakazakii contamination.